ETHICS AND ITS CONTRIBUTION TO THE QUALITY THAT THE PUBLIC ACCOUNTANT APP LIES IN PERU - Polar Falcón, Ernesto Augusto (2009)
As a professional broadcast of this article entitled: “Ethics and its contribution to the quality that apply public peruvian” is part of the results of research being undertaken in the year 2009, showing concern as preliminary, the need facilitate studies of the relationship between professional ethics and contribution to the quality, concepts and approaches presented in this important topic so that the reader will fit professionally and able to assess of a Control Program Quality and its applications. Also included is an explanatory table which there is practical coordination between professional ethics and contribution to quality, which consolidates a total overview of the topic. Show the comparison of two measures of Certified Public Accountants, to arouse interest in making an early application of this technique in the work of professional accountants in Peru. To sum up contain positive messages as a collaborative national accounting profession.